2020
DOI: 10.1055/a-1210-4830
|View full text |Cite
|
Sign up to set email alerts
|

How to read small bowel capsule endoscopy: a practical guide for everyday use

Abstract: Small bowel (SB) capsule endoscopy (SBCE) is often perceived by both patients and physicians as a "lightweight," noninvasive, comfortable procedure that is easily performed with little more than swallowing a pill and a glass of water. However, "easy to carry out" does not translate to ease of reading or interpretation. A SB capsule acquires thousands of images and generates a long video; however, clinically relevant findings are often seen in only a few frames. There is no way to direct or focus the camera, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
36
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(38 citation statements)
references
References 28 publications
0
36
0
2
Order By: Relevance
“…The first leap forward was done with in 2019, when a large multicenter Chinese study confirmed that a CNN‐based algorithm was able to accurately identify abnormalities in CE images and able to drastically reduce the CE reading times to around 6 min per video 24 . Recently, we alluded to the fact that CE is open to a high level of scrutiny and medicolegal challenge, as the recorded video data can be readily accessible for further on‐demand review 3 . AI solutions are not immune from such audits.…”
Section: Needsmentioning
confidence: 99%
See 3 more Smart Citations
“…The first leap forward was done with in 2019, when a large multicenter Chinese study confirmed that a CNN‐based algorithm was able to accurately identify abnormalities in CE images and able to drastically reduce the CE reading times to around 6 min per video 24 . Recently, we alluded to the fact that CE is open to a high level of scrutiny and medicolegal challenge, as the recorded video data can be readily accessible for further on‐demand review 3 . AI solutions are not immune from such audits.…”
Section: Needsmentioning
confidence: 99%
“…24 Recently, we alluded to the fact that CE is open to a high level of scrutiny and medicolegal challenge, as the recorded video data can be readily accessible for further on-demand review. 3 AI solutions are not immune from such audits.…”
Section: Needsmentioning
confidence: 99%
See 2 more Smart Citations
“…We report the case of a patient with episodes of obscure intestinal hemorrhage. Being uncommon, with nonspecific symptoms, SINETs cause diagnostic pitfalls, but images by capsule endoscopy (CE) and enteroscopy allow early diagnosis (Kim et al, 2020;Perez-Cuadrado-Robles et al, 2020;Rondonotti et al, 2020;Vasilakakis et al, 2020;Yoo et al, 2020). Intestinal bleeding of unknown origin is a common symptom of adenocarcinoma and gastrointestinal stromal tumors (GISTs), which may propitiate diagnostic challenges or misdiagnosis with NETs (Yoo et al, 2020).…”
Section: Introductionmentioning
confidence: 99%